A case study of the English class council of form 5B (Yuet Wah College, Macau school year 1999-2000): towards a participatory and transformative approach in education - Ching, Desiderio (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A mathematics curriculum or lower secondary schools in Macau - Wong, Kin Ming (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Mixed-methods Study on Teachers' Perceptions of the Use of Drama-in-education In Secondary English Classrooms in Macau - Leong, Si Kei (University of Saint Joseph, 2024)
Drama-in-Education (DiE) has been recognised as a valuable teaching pedagogy in the western world for decades, and yet it has not been fully or systematically adopted in the secondary English classes in Asian contexts, including Macau, despite the numerous reported advantages for English language teaching (ELT) in the past studies. This study explores Macau’s secondary school English teachers’ perceptions of utilising DiE in their classes. A mixed-methods research (MMR) approach was adopted in this study, consisting of three phases. First, pre-survey interviews were conducted to understand the potential major concerns about the choices of teaching approaches and the application of DiE of Macau’s secondary school English teachers. Subsequently, a questionnaire survey targeting local secondary school English teachers was administered, the results of which were cross-examined by, and integrated with, the results of two post-survey group interviews. While the results affirm the local secondary school English teachers’ positive view on DiE as an ELT pedagogy and identify their perceived advantages of DiE, the study indicates the over-determination of multi-faceted challenges to its implementation in Macau’s secondary education context. The study identifies and recommends necessary substantial changes to further the application of DiE in Macau’s secondary education milieu
Keywords: Drama; Drama-in-Education (DiE); English language teaching (ELT); English teachers; Macau; Secondary schools; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

A process-genre approch in curriculum development for lawyers in Macao: a case study - Fernandes, Raquel de Senna (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Action research, information technology and chemistry teaching in a Macau secondary school - Tchiang Van Man, Isabel (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An analysis of leadership in school - Ao, Wai Ngán (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An analysis of whether collaborative and cooperative work can improve students' reading and writing in English and enhance the development of higher order thinking - Lai, Pak Cheong (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into issues for leadership in culturally diverse schools - Hough, Elayne (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into students' views of the backwash effects of the English section of the joint admission examination for Macau four higher education institutions (languages and mathematics) - Bramley, Corinna Elaine (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into the competence-based approach and the person-centered approach for an all-round teaching approach, with reference to the aims of education - Un, Molly (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Citizenship and multiculturalism: towards an agenda for education for Macau - Chan, Chi Hou (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Class size, student achievement and pedagogical principles - Noruega, Charlot Francisca Fernandes (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

COGNITIVE PROCESSES IN ENGLISH SOURCE-BASED WRITING OF MACAO ENGLISH AS A FOREIGN LANGUAGE (EFL) UNIVERSITY STUDENTS - Peralta, Rachel Luna (University of Saint Joseph, 2024)
Source-based summary writing is an important aspect of academic writing at the undergraduate level; it includes summarizing and paraphrasing when producing texts in essay, report, or thesis formats. For university students whose second language or foreign language is English, source-based writing can be a challenging task as it involves and requires complex cognitive processes as well as reading-and-writing demands. Organized into three phases, this mixed method, small-scale exploratory feasibility case study investigated: (i) challenges and difficulties in online and offline English source-based summary writing of English as a Foreign Language (EFL) university students in Macao, identifying the cognitive and writing processes they experienced in a timed reading-writing task; and (ii) how to design and conduct interventions that could be used to diagnose, assess, and address essay challenges in source-based summary essay writing in everyday classroom sessions. Quantitative and qualitative data were collected through a summary online writing essay using Inputlog, a keystroke logging software, and retrospective think-aloud protocol in Phase One, a source-based summary essay writing task in a quasi-experiment in Phase Two, and a survey questionnaire and error analysis of pre-test and post-test essays of the control and experimental groups in Phase Three. The processes of reading and writing in English were found to be challenging and complex for EFL university students to perform in a limited time. As an initial exploratory feasibility, efficacy trial, deliberately small scale to address issues of risk, this study found that the diagnostic assessment tools and interventions had the potential to improve the summary writing processes and proficiency of EFL students, focusing on their cognitive writing skills in everyday class sessions. The thesis recommends scaling up the research in future studies, in terms of sampling and the duration of interventions designed to improve source-based summary essay writing and the cognitive writing processes that are part of this
Keywords: EFL university students; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph; cognitive processes; source-based writing

College choice: how students in Macau choose thier higher education institution - Coimbra, Diamantina Luiza do Rosario Sa (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum leadership and management - San, Pek Leng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Does gender make a difference in English language learning and attainment of secondary school students in Macau: a case study - Leong, On No (University of Saint Joseph, 2005)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

English learning strategies and strategy instruction: a mixed methods study of EFL students in higher education - Chan, Mei Lan (University of Saint Joseph, 2015)
This thesis investigates the Language Learning Strategies (LLS) used by English as a Foreign Language (EFL) nursing students of higher education in Macao and the effectiveness related to students’ learning outcomes by Strategy Instruction (SI). To date there has been no literature in the area of SI among the Macao Chinese EFL higher education students on teaching all LLS groups, and on four main English skills to look at its effects on learning processes and outcomes at the same time, and this study starts to fill the gap. The research uses an embedded mixed methods research design in phase one and an embedded mixed methods quasi-experimental design in phase two. Phase one aimed to identify students’ LLS use. The findings revealed that students’ cognitive, metacognitive and compensatory strategies were used more than affective, memory-related and social strategies, and overall they used a medium to low level of LLS. In phase two, the effects of SI on students’ changes of LLS use, their proficiency and English learning processes were identified. After SI, students used LLS both more widely and frequently in all four main English skills. Most students’ motivation and self-confidence were enhanced. After SI the affective group of strategies in the treatment group statistically significantly improved, with a moderate effect size, from that of the comparison group. It was found that the widely used Strategy Inventory for Language Learning questionnaires by Oxford (1989c) had limited statistical power and some conceptual confusion. Recommendations are made for policy and practice of EFL instruction
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

First year parenting and infant development: some implications for parenting education - Yan, Son U. (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Knowledge management in a Macao public sector bureau: a case study - Tai, Kin Ip (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Learning English in Macao - Cheong, Kit U. (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Misbehavior in school: problems and solutions - Cheong, Chun Cheng (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation as a key factor in the learning of English as a second language in Macau - Chiang, In Wa (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parents, students and secondary schools in Macao - Tchiang, Van Man (University of Saint Joseph, 2009)
Macao, a developing city, has been undergoing rapid and significant changes economically, culturally, and socially, partly as a consequence of the changes to the economy brought about by the gaming and tourism industry. Changes in Macao have had a major impact on its schools. Parents have a significant impact on students in school, and Macao’s secondary schools are having to handle a range of challenges and problems brought by students and their parents, many of these as a result of the changes in the wider society of Macao. The response of many schools to the challenges faced is limited, and they understate and under-use the important role played by more developed forms of parental involvement in schools. This study examines the nature, scope and extent of the problems that secondary schools in Macao are having to handle from parents and students, how the schools are handling them, and what needs to be done in order to address the problems and handle them more effectively. Through a large scale survey, interviews and a small scale questionnaire, the thesis identifies key problems facing the schools from students and parents, and it reveals that many of Macao’s secondary schools are ill-equipped to handle these, and there are many signs that the problems are becoming more acute. The thesis finds that negative parental behavior has had a stronger effect on students than positive parental behavior, and it finds that there are several reasons why the schools, in their present state, cannot address these matters effectively. A significant gap is found between what the schools indicate they should be doing and what they are actually doing to address increased parental involvement in order to impact positively on Macao’s students. Recommendations are made for intervention and action
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

PERCEPTIONS OF, AND ATTITUDES TO CATHOLIC SCHOOLS’ IDENTITY AND ETHOS IN MACAO: TOWARDS A COMMON FRAMEWORK OF CATHOLIC SCHOOLS’ IDENTITY - The Reh, Lawrence (University of Saint Joseph, 2024)
The thesis identifies concerns preserving, maintaining, and developing the Catholic identity of Catholic schools in Macao, the largest providers of schooling whilst being a minority religion, and with its teachers, parents, and students coming from Catholic and non-Catholic backgrounds, cultures, and values. To understand the present situation of Catholic identity in Macao’s Catholic schools, manifesting itself in part through the Catholic ethos of schools, and to identify key features, mission, vision, values, and areas for the development of Catholic identity, together with its presence and practices, this thesis reports a study of the perceptions of, and attitudes to, Catholic identity held by three key stakeholder parties in a carefully chosen representative selection of Catholic schools: teachers, parents, and students. The thesis reports their views on what the Catholic schools are currently doing in the areas of Catholic identity, and what they consider that they should be doing in these areas. The areas of focus draw on scholarship and teachings on Catholic identity, with particular emphasis placed on documents on Catholic identity and ethos from the Vatican, Archbishop Miller, and Monsignor Stock. A large-scale empirical survey here found that there was considerable support for Catholic schools in Macao, their identity, ethos, and values from the three parties. Two emergent patterns of findings are reported concerning the steps that Catholic schools were taking to promote their identity: (a) what Catholic schools should be doing concerning Catholic identity received consistently higher scores than what they were currently doing; and (b) consistently higher support for Catholic identity came from the teachers, slightly less so from the parents, and slightly less than that from the students. The study conducted a follow-up, small-scale study to investigate why these might be the case, and it suggested that the combination of Catholic values and Chinese cultural features might explain the findings on Catholic identity in the schools. The study identifies areas for possible development of, and improvements to, the identity of Catholic schools, that take account of the local cultural contexts and the teachings of the Catholic church on identity, and how these might be addressed in practice
Keywords: Catholic Schools' Ethos; Catholic Schools' Identidy; Catholic schools; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Perspectives on extra-curricular activities in a secondary school: a survey - Lai, Ka Lon (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

SENIOR LEARNERS, ANDRAGOGY, GERAGOGY, AND SYNTHETIC PHONICS: A CASE STUDY - Bhroin, Aine Ni (University of Saint Joseph, 2023)
Although there is a substantial body of research on the second language acquisition of adults, there is little specific research on the learning experiences of senior and very senior adults. This thesis investigates and discovers the experience of being a senior from a traditional Confucian Heritage Culture aged between 55 and 75 years old, learning English as a foreign language through various interventions, including, the introduction of an adapted version of synthetic phonics to improve pronunciation, alongside the use of andragogical and geragogical principles to accommodate and encourage the development of agency and self-directed learning. This research adopted a case study methodology to investigate the lived experiences of seniors, and investigated the participants’ subjective constructions of the situation, learning experiences, challenges, circumstances, needs, and wants with regard to the situation. Therefore, an open and exploratory case study design was selected to understand the participants and report the findings. Furthermore, this thesis identifies the challenges faced by senior and very senior learners who are post-work and post-family rearing to make recommendations from the findings to complement, enhance and empower their learning
Keywords: ANDRAGOGY; GERAGOGY; SENIORS; SYNTHETIC PHONICS; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Student councils and citizenship eduation: Principles and practices - Tang, Sut Leong (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Suicide prevention in schools: are Macau's teachers prepared? - Diaz, Javier Suarez (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teacher stress in the Macau workplace - Garcia, Alejandro Salcedo (Inter-University Institute of Macau, 2008)

Teachers’Perceptions of Performance Appraisal in a Secondary School in Asia: A Case Study - Potger, Matthew Rodney (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers stress in the workplace in Macau: an investigation - Chan, Chao Hou (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The implementation of the theory of multiple intelligences in the primary section of a school in Macau - Vong Ka I, Catherine (Macau Inter-University Institute, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The use of multimedia in primary teaching: a case study - Lam, Szui Lui (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Understading parental involvement from a socio-cultural perspective - Ao, Sio Heng (Macau Inter-University Institute, 2003)
Keywords: Parent-teacher relationship; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using Collaborative learning and blended learning with Macau undergraduate students inside and outside university classroom - Monteiro, Elisa Pack Jon Fong Rendall (University of Saint Joseph, 2015)
This thesis reports a mixed methods empirical research which included a university-wide survey and action research in form of a quasi-experiment in collaborative blended learning (CBL) with Macau undergraduate students. The intervention embodied the principles of social constructivism and investigated the putative benefits and challenges of CBL. The purpose of the study was to identify how to promote effective CBL in undergraduate students and to increase effective learning, motivation, autonomy, empowerment, and communication. It found that only small improvements to students’ CBL took place over time, and found that the students needed specific instruction, practice and development in how to collaborate, both with and without online learning. Despite being in a world-leading, enriched digital environment, the students were new to collaboration and online learning. Students discovered and appreciated the benefits and challenges to collaboration and CBL largely by doing it. The thesis shows that CBL does not release teachers from their instructional and pedagogical roles; rather they place teachers at the heart of effective practice and improvements. The study underpins the need for explicit training of students in CBL. It identifies several strategies and tools which can be useful to promote effective genuine CBL
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph